Characterization of oil extracted from the kernel of the fruit of cumare’s palm (Astrocaryum chambira Barret) (2018)
The objective of this research was the physicochemical characterization, fatty acid composition and Vitamin E content of oil extracted from the kernel of the fruit of cumare´s palm (Astrocaryum chambira). The plant material used in this research was collected in Caney-Restrepo, km 12 in the department of Meta-Colombia. The oil extraction process was performed by the soxhlet method using n-hexane as solvent, applying a unifactorial three-level experimental design to determine the most appropriate mass: solvent ratio. The percentage of lipids in dry basis of the kernel samples was 46.88 ± 0.73, which corresponds to the ratio 5 g of dry sample: 150 mL of solvent. The results of the physicochemical parameters were: density at 25 °C 0.9171 ± 0.003 g mL-1, refractive index at 40 °C 1.4518 ± 0.0004, iodine index 8.28 ± 0.60 g I2 100 g-1 oil, saponification index 246.66 ± 0.69 mg KOH g-1 oil, the percentage of acidity 0.248% ± 0.002 and the acid index 0.694 ± 0.006 mg KOH g-1 oil. The fatty acid profile presented a higher proportion of saturated (91.6%) than unsaturated (8.3%), likewise the analysis showed that lauric acid is the most abundant (48.6%) followed by myristic (29.8%), palmitic (6.7%), oleic (5.7%) and linoleic (2.5%). Based on the results obtained in the presentstudy, data reported in the literature and regulations related to the use of oils of vegetable origin, this oil shows a great potential to be used as raw material in the food, pharmaceutical and oleochemicalindustry is feasible. However, it is recommended to perform additional tests in order to reaffirm their use in them.